2020
DOI: 10.3390/pathogens9020123
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophil Granule Exocytosis in Response to Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis rarely causes disease in the immunocompetent, but reported cases of soft tissue infection describe abscess formation requiring surgical debridement for resolution. Neutrophils are the first innate immune cells to accumulate at sites of bacterial infection, where reactive oxygen species and proteolytic enzymes are used to kill microbial invaders. As these phagocytic cells play central roles in protection from most bacteria, we assessed human neutrophil phagocytosis and granule exocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…LAM is associated with lactosylceramide-enriched lipid rafts localized on the neutrophil membrane to disrupt the signaling of the tyrosine-protein kinase, inhibiting the association of hematopoietic cell kinase (Hck) with Lyn tyrosine kinase to prevent phagolysosome formation, cytokine production, degranulation, and respiratory burst. Moreover, reports suggest that LAM recognition by neutrophils regulates the exocytosis of secretory vesicles (Miralda et al, 2020). Together, these results provide further support for the hypothesis that LAM insertion into lipid rafts regulates vav phosphorylation, consequently downregulating ras-related protein (Rab27a) and limiting the traffic of azurophilic granules by blocking the GTP hydrolysis (Figure 3B).…”
Section: Modulation Of the Innate Immunity By Lamsupporting
confidence: 78%
“…LAM is associated with lactosylceramide-enriched lipid rafts localized on the neutrophil membrane to disrupt the signaling of the tyrosine-protein kinase, inhibiting the association of hematopoietic cell kinase (Hck) with Lyn tyrosine kinase to prevent phagolysosome formation, cytokine production, degranulation, and respiratory burst. Moreover, reports suggest that LAM recognition by neutrophils regulates the exocytosis of secretory vesicles (Miralda et al, 2020). Together, these results provide further support for the hypothesis that LAM insertion into lipid rafts regulates vav phosphorylation, consequently downregulating ras-related protein (Rab27a) and limiting the traffic of azurophilic granules by blocking the GTP hydrolysis (Figure 3B).…”
Section: Modulation Of the Innate Immunity By Lamsupporting
confidence: 78%
“…Avirulent mycobacteria, such as M. smegmatis , do not trigger the degranulation of secretory, primary and secondary granules in human neutrophils, even upon microbial opsonization. However, opsonized M. smegmatis elicits a time- and presumably CR-dependent secretion of active matrix metalloproteinase 9 (MMP9), which is stored in tertiary granules [ 123 ]. Attenuated mycobacteria, such as M. bovis BCG, promote release of the TNF-related apoptosis-inducing ligand TRAIL/APO-2L, which is mainly present in the primary and secretory vesicles of human neutrophils [ 124 ].…”
Section: The Infected Neutrophil: Events Within and Its Fatementioning
confidence: 99%
“…The studies indicated that the clearance ability of host cells for a pathogen was prominently determined by autophagy [16,58]. Previous studies also found that nonpathogenic M. smegmatis within alveolar epithelial cells may be eliminated or replicated, mainly depending on the intracellular mycobacterial load and the effectiveness of the immune responses [11,[59][60][61]. On the basis of TLR2 activation, Rubicon interacts with one subunit of the NADPH oxidase complex, enhancing phagosomal trafficking to induce ROS release and the expression of inflammatory cytokines to defend against invaders [18,19].…”
Section: Discussionmentioning
confidence: 98%